Edible wild mushroom tourism as a source of income and employment in rural areas. The case of Castilla y León - de Frutos Madrazo, P.; Martínez-Peña, F.; Esteban, S. (Forest Systems, 2012)
Edible wild mushroom picking is becoming an important source of income in rural areas. The wide range of activitieswhich add value to mycological production (initial sale, transformation, marketing, etc.) include those related to tourismwhich can attract visitors to mushroom producing areas, leading to so-called mycological tourism. To date, no researchexists quantifying the importance thereof in rural areas endowed with such resources. The present research provides thefirst model to estimate this activity’s contribution to the economy of rural areas in the region of Castilla y León. The mainfinding to emerge evidences a close link between influx of visitors, who come principally to pick, and mycological productivityin the region. Based on this relation, we estimate four key variables to determine the impact which said activityhas on the regional economy as a whole: the number of overnight stays and trips made by mycological tourists, as wellas associated expenditure and employment created. Findings underscore the importance of this activity in the regionaltourism industry and point to its significance as a major market niche, particularly during the hotel low season. The needfor public administrators to implement a related management policy is also inferred.